2007
DOI: 10.1210/en.2006-0732
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Externalization of Annexin 1 in the Adrenal Gland: Structure and Function of the Adrenal Gland in Annexin 1-Null Mutant Mice

Abstract: Annexin 1 (ANXA1) is a member of the annexin family of phospholipid- and calcium-binding proteins with a well demonstrated role in early delayed (30 min to 3 h) inhibitory feedback of glucocorticoids in the hypothalamus and pituitary gland. This study used adrenal gland tissue from ANXA1-null transgenic mice, in which a beta-galactosidase (beta-Gal) reporter gene was controlled by the ANXA1 promoter, and wild-type control mice to explore the potential role of ANXA1 in adrenal function. RT-PCR and Western blott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Interestingly, ANXA1 is also expressed in the adrenal cortex, and as observed in other tissue, its expression and activity is regulated by CORT (Davies et al 2007). Remarkably, the same study also showed that ACTH stimulation of isolated adrenal gland obtained from ANXA1-null mice exhibited a greater CORT response compared to adrenal obtained from WT mice, suggesting an involvement of ANXA1 in the inhibition of CORT synthesis.…”
Section: Intra-adrenal Glucocorticoid-mediated Negative Feedbackmentioning
confidence: 52%
“…Interestingly, ANXA1 is also expressed in the adrenal cortex, and as observed in other tissue, its expression and activity is regulated by CORT (Davies et al 2007). Remarkably, the same study also showed that ACTH stimulation of isolated adrenal gland obtained from ANXA1-null mice exhibited a greater CORT response compared to adrenal obtained from WT mice, suggesting an involvement of ANXA1 in the inhibition of CORT synthesis.…”
Section: Intra-adrenal Glucocorticoid-mediated Negative Feedbackmentioning
confidence: 52%
“…ANXA1 expression is stimulated by 17b-estradiol, in the anterior pituitary in vivo (Davies et al 2007a(Davies et al , 2007b. ANXA1 has an effect on cell growth, differentiation, apoptosis, membrane fusion, endocytosis, and exocytosis (John et al 2004).…”
Section: Gene Analysismentioning
confidence: 99%
“…To demonstrate this, we carried out a study including pharmacological intervention with dexamethasone suppression as well as stimulation with an ACTH analog (Synacthen). ACTH is thought to be an acute regulator of aldosterone synthesis in stress situations (Muller 1995, Davies et al 2007. To demonstrate that there were clear increases and decreases in the production of aldosterone under the circumstances of the study and to make sure that there was definite hyper-and hypoplasia of the adrenal gland under stimulation and suppression we used a previously established protocol (Coll et al 2006).…”
Section: Aldosterone and Acth In Micementioning
confidence: 99%
“…Currently, there is a lack of longitudinal and systematic studies addressing adrenal gland growth and function as well as circulating aldosterone concentrations in mouse models. Plasma concentrations of corticosterone are relatively high and are therefore unproblematic to measure in mice (Weber et al 1999, Coll et al 2004, Wang et al 2004, Karpac et al 2005, Lee et al 2005, Sausbier et al 2005, Schmidt et al 2006, Davies et al 2007), whereas measurement of aldosterone can be problematic due to the low concentrations found in plasma and the limited amounts which can be collected from mice when repeated measurements must be carried out.…”
Section: Introductionmentioning
confidence: 99%